Deep Brain Stimulation for Refractory Focal Epilepsy: Unraveling the Insertional Effect up to Five Months Without Stimulation. Issue 2 (12th February 2021) - Thuberg, Dominik; Buentjen, Lars; Holtkamp, Martin; Voges, Jürgen; Heinze, Hans‐Jochen; Lee, Harim; Kitay, Ann‐Yasmin; Schmitt, Friedhelm C.
Abstract: Introduction: Following electrode implantation, a subgroup of patients treated with deep brain stimulation (DBS) for focal epilepsy exhibits a reduction of seizure frequency before stimulation is initiated. Microlesioning of the target structure has been postulated to be the cause of this "insertional" effect (IE). We examined the occurrence and duration of this IE in a group of patients with focal epilepsy following electrode implantation in the anterior nuclei of the thalamus (ANT) and/or nucleus accumbens (NAC) for DBS treatment. Materials and Methods: Changes in monthly seizure frequency compared to preoperative baseline were assessed one month (14 patients) and five months (four patients) after electrode implantation. A group analysis between patients with implantation of bilateral ANT‐electrodes (four patients), NAC‐electrodes (one patient) as well as ANT and NAC‐electrodes (nine patients) was performed. Results: In this cohort, seizure frequency decreased one month after electrode implantation by 57.1 ± 30.1%, p  ≤ 0.001 (compared to baseline). No significant difference within stimulation target subcohorts was found ( p  > 0.05). Out of the four patients without stimulation for five months following electrode insertion, three patients showed seizure frequency reduction lasting two to three months, while blinded to their stimulation status. Conclusion: An IE might explain seizure frequency reduction in our cohort. This effect seems to be independent of the number of implanted electrodes and of the target itself. The time course of the blinded subgroup of epilepsy patients suggests a peak of the lesional effect at two to three months after electrode insertion.